Targeting Heat Shock Proteins for Enhanced Apoptosis in Hyperthermic Breast Cancer Therapy Using Nanoquercetin and Nanocobalt Ferrite - Neamah, Alaa Sameer; Ghorbani, Raziyeh; Ahadian, Mohammad Mahdi; Hosseinzadeh, Simzar; Kazemi, Bahram (Journal of Contemporary Medical Sciences, 2025)
Objectives: The expression of heat shock proteins (hsps) in cells is dependent on cell stress and the high temperature of hyperthermia elevates them. Therefore, consideration of an attenuator of this pathway is needed. Methods: After preparation and characterization of both nanoquercetin and magnetic nanoparticles, MCF7 cell line treated to determine the IC50 of both nanoparticles using MTT assay. The percentage of radical levels in all groups was investigated using DPPH technique. Also, Real-Time PCR was utilized to reveal the regulation of hsps and apoptotic genes. Results: The diameter of the nanocobalt ferrite was 8.08 ± 2.5 nm indicating a soft-ferromagnetic property due to its zero coercivity. Also, the nanoquercetin exhibited a size of 42.42 ± 13.26 nm after encapsulation by chitosan. FTIR spectroscopy presented specific bands such as 1640, 1560 and 1380 cm-1 for amide I, II and III and 1600 and 1400 cm-1 for C=C stretching in aromatic rings, respectively for both chitosan and quercetin. The cell viability by MTT assay were 10 and 0.6 mg/ml for cobalt ferrite and quercetin as IC50 concentrations. After applying hyperthermia with a frequency of 350 kHz and a treatment duration of 10 min, the highest degree of radical inhibition was observed in the combination condition under hyperthermia, with a value of 21.03 ± 0.2 %. Moreover, the Bax/Bcl2 ratio of 6.66 in the composite group suggests an apoptotic fate for the cells. The composite and nanoquercetin treatments showed the highest fold changes of 1.4 and 43 for caspase 3. In contrast, caspase 8 exhibited values of 25 and 0.25 for these groups, respectively. Conclusions: The treatment of cells with a blocker of hsps such as quercetin increases the yield of hyperthermia. However, more investigations are needed, particularly in animal models to introduce this nanoformulation for clinical trials.